Is Twitter an Alternative Medium? Comparing Gulf Coast Twitter and Newspaper Coverage of the 2010 BP Oil Spill - Watson, Brendan R. (Communication Research, 2016)
This study compares Gulf Coast journalists and Twitter users’ coverage of the BP oil spill. In addition to examining authors’ attitudes toward and coverage of the BP oil spill, the study examines community-level variables that shaped attitudes and coverage. The community structure literature has suggested that news media in smaller, more homogeneous communities, which are economically dependent on a polluting industry (as are many communities along the Gulf Coast), are more reticent to be critical in their coverage of pollution. Scholars have suggested, though, that the Internet transcends local geography and that the Internet is more open to alternative perspectives. This study suggests, though, that while the distribution of online content may make local geography less relevant, its production is still rooted in local communities. As a result, Tweets about the oil spill were shaped by many of the same social and economic forces that shaped journalists’ coverage.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE0NTY1ODk2